Inertial focusing of a dilute suspension in pipe flow - Aouane, Othmane; Sega, Marcello; Baeuerlein, Bastian; Avila, Kerstin; Harting, Jens (Physics of Fluids, 2022)

Structure and rheology of suspensions of spherical strain-hardening capsules - Aouane, Othmane; Scagliarini, Andrea; Harting, Jens (Journal of Fluid Mechanics, 2021)
We investigate the rheology of strain-hardening spherical capsules, from the dilute to the concentrated regime under a confined shear flow using three-dimensional numerical simulations. We consider the effect of capillary number, volume fraction and membrane inextensibility on the particle deformation and on the effective suspension viscosity and normal stress differences of the suspension. The suspension displays a shear-thinning behaviour that is a characteristic of soft particles such as emulsion droplets, vesicles, strain-softening capsules and red blood cells. We find that the membrane inextensibility plays a significant role on the rheology and can almost suppress the shear-thinning. For concentrated suspensions a non-monotonic dependence of the normal stress differences on the membrane inextensibility is observed, reflecting a similar behaviour in the particle shape. The effective suspension viscosity, instead, grows and eventually saturates, for very large inextensibilities, approaching the solid particle limit. In essence, our results reveal that strain-hardening capsules share rheological features with both soft and solid particles depending on the ratio of the area dilatation to shear elastic modulus. Furthermore, the suspension viscosity exhibits a universal behaviour for the parameter space defined by the capillary number and the membrane inextensibility, when introducing the particle geometrical changes at the steady state in the definition of the volume fraction.
Keywords: Biological Fluid Dynamics: Capsule/cell dynamics; Complex Fluids: Suspensions; Non-Newtonian Flows: Rheology